2009
DOI: 10.1146/annurev.publhealth.031308.100147
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects of Combat: A Life-Course Perspective

Abstract: Armed combat (also termed war or armed conflict) has profound direct and indirect impacts on the long-term physical and mental health of both military personnel and noncombatant civilians. Although most research has focused on immediate and short-term health consequences of war, an increasing number of studies have focused on the long-term health consequences for both veterans of military service and noncombatant civilians. However, these long-term studies focus almost entirely on posttraumatic stress disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 47 publications
2
60
0
3
Order By: Relevance
“…However, psychological stresses associated with terrorism, war and one-sided violence arising from displacement, loss, grief and fear, social isolation, insecurity, loss of status and community, and witnessing and experiencing acts of violence such as summary execution, rape and assassinations can manifest in a variety of mental disorders. These disorders include a variety of depressive, anxiety and psychotic disorders (de Jong et al, 2007;DiMaggio and Galea, 2006;Levy and Sidel, 2009;Priebe et al, 2010), many of which are highly comorbid with substance use disorders (Compton et al, 2007;Hasin et al, 2007). Excessive substance use may also reflect self-medication for these psychiatric conditions, thereby increasing incidence and severity of substance use disorders in conflictaffected populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, psychological stresses associated with terrorism, war and one-sided violence arising from displacement, loss, grief and fear, social isolation, insecurity, loss of status and community, and witnessing and experiencing acts of violence such as summary execution, rape and assassinations can manifest in a variety of mental disorders. These disorders include a variety of depressive, anxiety and psychotic disorders (de Jong et al, 2007;DiMaggio and Galea, 2006;Levy and Sidel, 2009;Priebe et al, 2010), many of which are highly comorbid with substance use disorders (Compton et al, 2007;Hasin et al, 2007). Excessive substance use may also reflect self-medication for these psychiatric conditions, thereby increasing incidence and severity of substance use disorders in conflictaffected populations.…”
Section: Discussionmentioning
confidence: 99%
“…As mulheres refugiadas enfrentaram muitas vezes acontecimentos que lhe ameaçaram a vida e a violência sexual não só no país de origem, mas também nos campos de refugiados e até mesmo no pais anfitrião (Collins, Zimmerman, & Howard, 2011). O impacto da violência sexual e da violação em mulheres refugiadas vítimas da guerra mereceu a atenção de alguns estudos tendo-se observado depressividade, evitamento de pensamentos ou conversas acerca do trauma e ideação suicida (Levy & Sidel, 2009). A separação das crianças que ficaram para trás é também uma experiência muito angustiante para as mulheres (Collins et al, 2011).…”
Section: Mulheres E Questões De Génerounclassified
“…A perda de um dos progenitores está associada a maior incidência de PTSD e de depressão sendo as crianças que vivem com ambos os progenitores as que apresentam menos problemas psicológicos (Levy & Sidel, 2009). Montgomery (2011) numa revisão de estudos elaborados sobre jovens refugiados do Médio Oriente a residir na Dinamarca encontrou não propriamente PTSD especifica mas antes uma variabilidade de sintomas.…”
Section: Crianças E Idososunclassified
“…PTSD is common among combatants, and child soldiers are known to suffer from a much higher than average incidence of psychological disturbances and mental illness [64][65][66][67]. PTSD is also found in civilian populations in both women and children [68,69]. De Jong et al showed that PTSD and anxiety disorder were the most common mental illnesses in all populations, and exposure to violence increased their likelihood in the four conflict zones of Algeria, Cambodia, Ethiopia and Palestine [70].…”
Section: Maternal Exposurementioning
confidence: 99%